1982
DOI: 10.1073/pnas.79.23.7346
|View full text |Cite
|
Sign up to set email alerts
|

Cell types and morphogenesis in the mammary gland.

Abstract: Cell types present in the mammary gland and their evolution were studied by labeling female rats with radioactive thymidine at various phases of the estrus cycle. The results suggest that the stem cells for mammary development are present in the terminal end buds and that they generate a lineage for lumenal cells and possibly a distinct one for myoepithelial cells. Growth and differentiation are controlled by both hormones and local factors.The mammary. gland is the site of very frequent cancers in humans as. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1
5

Year Published

1989
1989
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 7 publications
3
34
1
5
Order By: Relevance
“…12,13,34,58,71 Briefly, the mammary bud was identifiable at PCD 13.5, after which it slowly developed into ducts until puberty. The pubertal mammary gland (21 and 42 days of life) was characterized by the formation of terminal end buds and acini by 21 days of age, and were most prominent and more numerous at 42 days of age.…”
Section: Mammary Morphogenesis and Data Poolingmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13,34,58,71 Briefly, the mammary bud was identifiable at PCD 13.5, after which it slowly developed into ducts until puberty. The pubertal mammary gland (21 and 42 days of life) was characterized by the formation of terminal end buds and acini by 21 days of age, and were most prominent and more numerous at 42 days of age.…”
Section: Mammary Morphogenesis and Data Poolingmentioning
confidence: 99%
“…3,57 These changes in keratin expression during mammary gland development are important because the formation of cancer in humans and in mice is influenced by developmental changes in the mammary gland at the time of oncogenesis. 13,51 The postpubertal mammary gland in rats, mice, and humans is composed of a branching ductal system ending in specialized lobules. The entire mammary tree is lined by an inner layer of luminal cells and an outer layer of basal cells, which often are referred to as myoepithelial cells.…”
mentioning
confidence: 99%
“…Lobules are a group of alveoli branched from the main duct. ABs generally consist of 3-5 blind ductules in a cluster [27,28]. In this study, no attempt was made to distinguish between ABs and lobules.…”
Section: Mammary Whole Mountsmentioning
confidence: 99%
“…The end buds comprise two epithelial cell types: an outer layer of cap cells and an inner solid mass of body cells. Looking at the dynamics in the growing end bud by time-lapse video microscopy and thymidine labeling, it has been reported that the basal cap cells give rise to myoepithelial cells, by maturation along the subtending duct, as well as to body cells, which comprise the later luminal epithelial cells by migration into the central cord of epithelial cells (Williams and Daniel, 1983;Dulbecco et al, 1982). Thus, cap cells have been ascribed stem cell-like properties, which fits well with their low level of differentiation.…”
Section: A Morphologymentioning
confidence: 89%